Reversible and Selective Interconversion of Hydrogen and Carbon Dioxide into Formate by a Semiartificial Formate Hydrogenlyase Mimic - Sokol, Katarzyna P. (2020)
The biological formate hydrogenlyase (FHL) complex links a formate dehydrogenase (FDH) to a hydrogenase (H2ase) and produces H2 and CO2 from formate via mixed-acid fermentation in Escherichia coli. Here, we describe an electrochemical and a colloidal semiartificial FHL system that consists of an FDH and a H2ase immobilized on conductive indium tin oxide (ITO) as an electron relay. These in vitro systems benefit from the efficient wiring of a highly active enzyme pair and allow for the reversible conversion of formate to H2 and CO2 under ambient temperature and pressure. The hybrid systems provide a template for the design of synthetic catalysts and surpass the FHL complex in vivo by storing and releasing H2 on demand by interconverting CO2/H2 and formate with minimal bias in either direction.